2014
DOI: 10.1080/15017419.2013.868823
|View full text |Cite
|
Sign up to set email alerts
|

Body, participation and self transformations during and after in-patient stroke rehabilitation

Abstract: This study explores stroke survivors' experience of being part of an institutional rehabilitation context and what it means for the immediate experience of discharge home. The aim is to develop a deeper understanding of how the dynamic phenomenon body, participation in everyday life and sense of self interrelates and changes through stroke survivors' movement in and between the two contexts and what this phenomenon means for stroke survivors' process of change and well-being in the early rehabilitation traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…However, stroke survivors have reported that re-integration into the community is nevertheless the most challenging part of recovery (7,8), during which time the extent of stroke-related disability typically becomes most apparent (9). Many stroke survivors report social isolation, exclusion and inactivity in their daily lives (10,11), a condition which people 5 years post-stroke have termed home-bound life (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, stroke survivors have reported that re-integration into the community is nevertheless the most challenging part of recovery (7,8), during which time the extent of stroke-related disability typically becomes most apparent (9). Many stroke survivors report social isolation, exclusion and inactivity in their daily lives (10,11), a condition which people 5 years post-stroke have termed home-bound life (12).…”
Section: Introductionmentioning
confidence: 99%
“…A stroke trajectory has been described as a biographical work [5][6][7], where the focus has been on the survivor's increased attention to the body's actual state, to mobilisation and to rethinking their lives and self-concept [7], as well as their struggles to reconstruct continuity in life [6,8]. Others have stressed that the stroke does not necessarily result in ''biographical disruption'' as the stroke does not necessarily appear as an immediate crisis for that person, and that initially, the long-term impact on self and everyday life becomes the main concern [9,10]. The subject might also construct a continuity of self by drawing on other people's accessible and powerful discursive resources such as age, expectations of ageing processes, religious beliefs or other life events such as previous illness experiences [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The patients often have reduced capacity because of the injury and the transition between the institution and home constitutes a vulnerable phase (54,55). The institutional rehabilitation environment allows patients to mobilize focus and energy on their physical recovery, whereas new challenges appear when discharged (56). The shift from the hospital setting to continued rehabilitation in the patients' home communities also involves additional efforts to re-establish everyday life, expanding the context in which the rehabilitation take place.…”
Section: Discussionmentioning
confidence: 99%